2012
DOI: 10.2298/bah1202333s
|View full text |Cite
|
Sign up to set email alerts
|

Feed restriction in broiler chickens production

Abstract: The feed restriction program is on of the main techniques in growth curve manipulation for increasing production efficiency in broiler chicken. Quantities and qualitative feed restriction are procedures that can be used to manipulate the feeding strategies of poultry in order to decrease growth and metabolic rate to some extent and so alleviate the incidence of some metabolic diseases such as ascites, lameness, mortality, and sudden death syndrome and so improving feed conversion and reducing feed cost. Also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 89 publications
6
51
0
8
Order By: Relevance
“…However, published results indicated that FR increased survival rate due to less sudden death, ascites and skeletal disorders (24,25) . Lymphoid organs, antioxidant status and im mune markers FR regimen did not have significant influence on lymphoid organs (Table 2), total antioxidant capacity (TAC), malondialdehyde (MDA), Immunoglobulin M (IgM), Immunoglobulin G (IgG), HIIBD, HIAI, Lysosome activity (LyzA), BacA, PA and PI, but immunoglobulin A (IgA) significantly increased by 3.9 % compared to the control (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, published results indicated that FR increased survival rate due to less sudden death, ascites and skeletal disorders (24,25) . Lymphoid organs, antioxidant status and im mune markers FR regimen did not have significant influence on lymphoid organs (Table 2), total antioxidant capacity (TAC), malondialdehyde (MDA), Immunoglobulin M (IgM), Immunoglobulin G (IgG), HIIBD, HIAI, Lysosome activity (LyzA), BacA, PA and PI, but immunoglobulin A (IgA) significantly increased by 3.9 % compared to the control (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Various quantitative and qualitative methods of feed restriction are used in broilers to improve their efficiency of feed utilization and weight gain (Mahmood et al, 2007). Such methods result in temporary reduction of growth rate, while the normal weight of broilers can be attained on removal of feed restriction, thus improving the feed efficiency and decreasing the feeding cost (Mahmood et al, 2007;Sahraei, 2012). The objective of the present study was to evaluate the effect of limiting feeding time by three and six hours during the starter period on broiler chicks` performance.…”
Section: Introductionmentioning
confidence: 96%
“…The use of GPA for obtaining the fast growth usually increased the body fats of chicken that lead to high incidence of metabolic disorders, skeletal diseases and mortality [9]. Besides, the feed restriction is one of the main technique to decrease the incidence of metabolic diseases, carcass fat deposition, reduce maintenance requirement and improvement of feed efficiency in broiler chickens production, which enhance the growth and production efficiency [10].…”
Section: Introductionmentioning
confidence: 99%